Impact on postoperative complications of combined prehabilitation targeting co-existing smoking, malnutrition, obesity, alcohol drinking, and physical inactivity: a systematic review and meta-analysis of randomised trials [version 2; peer review: 2 approved] - Hanne Tønnesen; Ulla N Joensen; Robin Christensen; Mette Rasmussen; Susanne V Lauridsen; Sofie Anne-Marie S Jensen; Line N Lydom; Jacob Rosenberg (F1000Research, 2025)
Background This study aimed to compare the effect on postoperative complications of combined prehabilitation targeting predefined co-existing risky SNAP factors with usual preoperative routines in surgical patients. Methods This systematic review followed the PRISMA 2020 guideline and the protocol (CRD42022282611). Five databases were searched from inception to November 7, 2022 for randomised controlled trials on prehabilitation targeting ≥2 predefined risky lifestyles compared with usual preoperative routines. Risky lifestyles included Smoking, Nutrition (malnutrition and/or BMI>25), risky Alcohol intake, and Physical inactivity (SNAP). Primary outcome was postoperative complications ≤30 days. Cochrane’s risk-of-bias tool 2 was used and meta-analyses were conducted. GRADE was used to assess certainty of evidence. Results The search resulted in 20,862 records. At full-text screening, only two (120 participants) of 24 identified trials on combined SNAP intervention had ≥2 predefined risk factors and were included. One (n=110) on intensive physical and brief nutritional intervention to frail patients with colorectal cancer resection reported complication rates of 45% in both groups (relative risk (RR) 1.00, 95% CI 0.66 to 1.51). The other study (n=10, subgroup) on intensive alcohol and smoking intervention in patients with bladder cancer undergoing radical cystectomy, reported complications in 3/7 vs 3/3 participants. The meta-analysis estimated a RR of 0.79 (95% CI 0.41 to 1.51, I2 51%). Conclusion Two small of the 24 trials on prehabilitation targeted co-existing and predefined risky SNAP factors and the effect on postoperative complications is very uncertain. Future prehabilitation research involving patient needs is warranted.